2023
DOI: 10.21203/rs.3.rs-2614397/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of different Hb concentrations on the risk of gestational diabetes mellitus in women with thalassemia minor

Abstract: Backgrounds A few studies have focused on the effect of thalassemia and different Hb levels on pregnancy outcomes recently. However, to our knowledge, there are no studies on the effects of different levels of hemoglobin(Hb) on pregnancy outcomes in Chinese women with thalassemia minor. In the present research, we aimed to clarify the effect of different Hb levels on pregnancy outcomes and to further explore the association of different Hb levels and gestational diabetes mellitus (GDM) in pregnant women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Interestingly, the study conducted by Wang et al,(2023) suggested that high Hb concentration might be a trigger for GDM in Chinese pregnant women with thalassemia minor [20]. This highlights the need for further investigation into the relationship between Hb concentration and the development of GDM in pregnant individuals with thalassemia minor.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study conducted by Wang et al,(2023) suggested that high Hb concentration might be a trigger for GDM in Chinese pregnant women with thalassemia minor [20]. This highlights the need for further investigation into the relationship between Hb concentration and the development of GDM in pregnant individuals with thalassemia minor.…”
Section: Discussionmentioning
confidence: 99%